The Role of «Soft» State Support in Developing Large Business - A. A. Blokhin; E. S. Krivova (Мир новой экономики, 2022)
The article analyses the consequences of dividing large companies into priority and non-priority ones for the state by including them in the List of the system-forming companies and carrying out appropriate support procedures in relation to them. We have shown that such procedures for the state were rather institutional than financial and costly since support was transferred to large state-owned banks that carried out it while maintaining the principles of self-sufficiency of investments. Comparison of two samples of companies included in this List and their counterparts, not from the List demonstrates a clear difference in their dynamics before the adoption of the List and after it. Priority companies are steadily and many times (3–4 times) growing in terms of revenue, non-priority ones “stagnate”, remaining practically at the same level even at current prices. The almost one-time division of companies by priority in 2009 turned out to be stable over the next decade, which allows us to speak of the resulting redistribution of markets and their transformation in favour of the groups of leaders formed due to it in the respective industry markets. The analysis allows us to evaluate this example as a weak institutional impact, with a noticeable sectoral and macroeconomic effect. We noted that a change in the architecture of markets after the described impact leads not only to a change in the strategies of their participants but also to a restructuring of mechanisms of state regulation.